Hardesign vs Softdesign - Raffaella Fagnoni; Chiara Olivastri (Agathón)
Our thought on innovation starts from the dichotomy between the strong and the light design’s components: on the one hand opposed, on the other complementary. Hard is the process based on the consumerist model, Soft is more sustainable. Hard is the dimension of possession, Soft is that of access and sharing. Hard is the top-down process and Soft is the bottom-up process that values social innovation. The project tools are not records to be applied. They must adapt, be customized to the needs expressed by the people who are activating themselves in the structuring of answers. The role of designers today is to face our time challenges, to which the models used in the last century are unable to respond. It is to answer to the world’s change by performing the change in the project.